THE INFRARED THERMAL IMAGE-BASED MONITORING PROCESS OF PEACH DECAY UNDER UNCONTROLLED TEMPERATURE CONDITIONS - L. Z. Jiao; W. B. Wu; W. G. Zheng; D. M. Dong (Journal of Animal and Plant Sciences, 2015)
In this paper, we developed a monitoring method for identifying decayed fruit tissues and the degree of decay under the conditions of uncontrolled temperature and naturalconvection. The monitoring results showed that temperature differences between the decayed tissues and sound tissues were significant and varied with decayaggravation. The maximum temperature difference was 0.7 °C. After deducting the influence of the environmentaltemperature, we extracted and analyzed the infrared thermal images of the decayed tissues. The results indicated that the temperaturedifference between decayed and sound tissues can be used to identify the location and degree of decayed tissue. The paper provides the monitoring method of fruit surface decay and the extraction and calculation method of the decay area and degree.
Keywords: decay; uncontrolled temperature; infrared thermal imaging; image processing